OPTIMIZATION OF TEMPE MARKETING AND PRODUCTION IN TEMPE UMKM THROUGH FOCUS GROUP DISCUSSIONS (FGD) IN KEDUNGJAYA VILLAGE, KEDAWUNG DISTRICT, CIREBON REGENCY - Arin Arin; Gian Fitralisma; Winda Dwi Yanthi; Ade Febry Nur Fitriani; Amah Amalia; M. Anissul Fata; Suwaebit Suwaebit; Eva Noviana (Ann Publisher, 2025)
Abstract Background: This article discusses the role of students in the Community Service Program (KKN) in Kedungjaya Village, Kedawung District, Cirebon Regency, with a focus on optimizing the marketing and production of tempe in tempe UMKM through Focus Group Discussions (FGD). Aims: The purpose of this community service is to identify and analyze the role of KKN students in improving tempe marketing and production in Kedungjaya Village, as well as the positive impacts generated. Methods:This community service utilized Focus Group Discussions (FGD) to engage with tempe UMKM actors. KKN students from STIE Cirebon provided guidance on digital marketing strategies, social media management, and optimizing the use of marketplaces to enhance the marketing and production processes. Results: The results of the community service show that KKN students played a significant role in providing insights into digital marketing strategies, social media management, and optimizing the use of marketplaces for tempe UMKM. Positive impacts observed include an increase in the knowledge of UMKM actors in marketing their products, more efficient production management, and improved quality of the tempe products produced. Conclusion: Despite challenges in implementation, good collaboration between students, UMKM actors, and the village community is crucial for the success of this program. The role of KKN students has proven valuable in improving both the marketing and production aspects of tempe in Kedungjaya Village. Implementation: The main recommendation is to continue intensive mentoring, increase active participation from UMKM actors, and strengthen marketing and distribution infrastructure in Kedungjaya Village to ensure sustainable improvements in the tempe UMKM sector.